Considerations and inquiries about the dynamics of the Brazilian state facing the demands of schooling: instruments, dilemmas and complexity - Lemes, Sebastiao de Souza [UNESP] (Univ Federal Sergipe, 2021)
The aim of this study is to understand issues of public policy, government and governance in relation to Education in Brazil, making use, for this analysis, of an understanding of evaluative and managerial instruments, in addition to public policies aimed at school education, to understand the scenario built in national education. Under the guise of cognitive analysis of public policies and their foundations, the state of the art is mobilized to better understand and analyze the guiding concepts of this work, which also considers theories about a change in the bias of bureaucracy and its role in the state. In the end, it is noted that the actions of the Brazilian government, in line with international pressure and evaluation mechanisms, assume an interventionist and inefficient character, which places the equitable democratization of education, advocated in the 1988 Constitution, as a challenge yet to be reached and with many obstacles along the way.
Keywords: Assessment; Educational system; Public policy; Schooling; Territoriality